Emergency general surgery in the United Kingdom: A lot of general, not many emergencies, and not much surgery. Issue 3 (September 2018) - Ramsay, George; Wohlgemut, Jared M.; Jansen, Jan O.
Abstract : BACKGROUND: The provision of emergency general surgery services is a global issue, with important implications for patients and workforce. The aim of this study was to analyze the characteristics of emergency general surgical patients in the United Kingdom, with reference to diagnostic case mix, operative workload, comorbidity, discharge destination, and outcomes, to facilitate comparisons and future service development. METHODS: This is a cross-sectional population-based study based in the National Health Service in Scotland, one of the home nations of the United Kingdom. All patients aged 16 or older admitted under the care of a general surgeon, as an emergency, to a National Health Service hospital in Scotland, in 2016, were included. RESULTS: There were 81, 446 emergency general surgery admissions by 66, 498 patients. Median episode age was 53 years. There were more female patients than male (55% vs 45%, p < 0.0001). The most common diagnoses were nonspecific abdominal pain (20.2%), cholecystitis (7.2%), constipation (3.4%), pancreatitis (3.1%), diverticular disease (3.1%), and appendicitis (3.1%). Only 25% of patients had operations (n = 20, 292). The most frequent procedures were appendicectomy (13.1%), endoscopy (11.3%), and drainage of skin lesions (9.7%). Diagnoses and operations differed with age. Overall median length of stay was 1 day. With a 6-month follow-up, patients older than 75 years had a 19.8% mortality rate. CONCLUSIONS: Emergency general surgery in the United Kingdom is a high-volume, diagnostically diverse, and low–operative volume specialty with high short-term mortality rate in elderly patients. Consideration should be given to alternative service delivery models, which make better use of surgeons' skills while also ensuring optimal care for patients who are increasingly elderly and have complex chronic health problems. LEVEL OF EVIDENCE: Epidemiologic study, level III. Abstract : Supplemental digital content is available in the text.